Unveiling the protein-protein interactome of the RNA-binding protein Rev in HIV-1 infected T CD4+ lymphocytic cells - Truman, C (2021)
Human immunodeficiency virus type I (HIV-1) is a retrovirus that causes acquired immunodeficiency syndrome (AIDS) and affects ~38 million people worldwide. The HIV-1 protein Rev escorts under-spliced viral RNAs to the cytoplasm, overriding nuclear retention imposed by the host cell. Thus, Rev permits full viral gene expression and particle production. However, Rev is challenging to study as it is highly disordered, expressed at low levels and encoded by an open reading frame that overlaps other viral genes. Therefore, previous Rev research was largely performed under non-physiological conditions, leaving the physiological interactions and functions of Rev uncertain. Here, I engineered HIV-1 constructs that encode tagged Rev protein expressed to physiological levels. I used these constructs to immunoprecipitate Rev interactors in CD4+ cells, revealing the physiological interactome of Rev. Through meta-analysis of this novel interactome and previously published datasets, I provide evidence for a new connection between Rev-mediated export and HIV-1 virion assembly. Furthermore, I investigate the interactions of two packaged proteins, PURA and PURB, during HIV-1 replication, to reveal possible therapeutic targets. My research uncovers the localisation, interactions and functions of Rev during HIV-1 replication under conditions better approximating physiological conditions than previously used. This work thus provides highly valuable datasets to instruct new avenues of research on the HIV-1 infection cycle.